Triactome: Neuro–Immune–Adipose Interactions. Implication in Vascular Biology - Chaldakov, George Nikov; Fiore, Marco; Ghenev, Peter I.; Beltowski, Jerzy; Ranćić, Gorana; Tunçel, Neşe; Aloe, Luigi (Frontiers in Immunology, 2014)
Understanding how the precise interactions of nerves, immune cells and adipose tissue account for cardiovascular and metabolic biology is a central aim of biomedical research at present. A long standing paradigm holds that the vascular wall is composed of three concentric tissue coats (tunicae): intima, media, and adventitia. However, large- and medium-sized arteries, where usually atherosclerotic lesions develop, are consistently surrounded by periadventitial adipose tissue, we recently designated tunica adiposa (in brief, adiposa like intima, media, adventitia). According to present paradigm, atherosclerosis is an immune-mediated inflammatory disease featured by endothelial dysfunction/intimal thickening, medial atrophy and adventitial lesions associated with adipose dysfunction, whereas hypertension is characterized by hyperinnervation-associated medial thickening due to smooth muscle cell hypertrophy/hyperplasia. Periadventitial adipose tissue expansion is associated with increased infiltration of immune cells, both adipocytes and immunocytes secreting pro-inflammatory and anti-inflammatory (metabotrophic) signaling proteins collectively dubbed adipokines. However, the role of perivascular nerves and their interactions with immune cells and paracrine adipose tissue is not yet evaluated in such an integrated way. The present review attempts to briefly highlight the findings in basic and translational sciences in this area focusing on neuro-immune-adipose interactions, herein referred to as triactome. Triactome-targeted pharmacology may provide a novel therapeutic approach in cardiovascular disease.